PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN PADA MASKAPAI PENERBANGAN PT.GARUDA CITILINK RUTE PEKANBARU – JAKARTA - Widodo Putra; Endang Sutrisna (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study is a study to describe the Influence of Service Quality on Customer Loyalty on Airline PT.Garuda Citilink Pekanbaru Route - Jakarta. From the data obtained, from 2013 to 2016, the number of passengers using Citilink's carrier airline has decreased in 2016 and caused a decrease in passengers loyal to Citilink airlines. Problems that occur are less effective and efficient implementation and function of the company in meeting the quality of peyananan desired by the customer. The purpose of this research is to know the influence of service quality to customer loyalty at airline PT.Garuda Citilink Pekanbaru - Jakarta route and to know the inhibiting factors is less effective and efficient execution and function of company in fulfilling quality of peyananan desired by customer. The concept of the theory used is Quality of Service and Loyalty. This research uses quantitative method to test the influence between the two variables. Customers who are sampled amounted to 100 people. The type of data used is primary data with data collection methods using questionnaires that spread to 100 respondents. Data analysis method used in this research is a simple linear regression with the help of SPSS Software Version 17.0. The results of this study indicate the quality of service and customer loyalty in PT.Garuda Citilink Pekanbaru branch classified as less good and customer loyalty, based on the results obtained as a whole off Citilink airline route Pekanbaru-Jakarta route loyal enough or loyal to use Citilink aircraft carrier. Keywords: The Effect of Service Quality on Customer Loyalty on Airline PT.Garuda Citilink Pekanbaru – Jakarta